Identification of the Doctrine of Violent Extremism of Terrorist Networks in De-Radicalization Efforts - Wahyu Agung Sukhamdani; Mohamad Ismed (Program Pascasarjana Universitas Negeri Makassar, 2023)
Terrorists are not suddenly born, there is a process in which the process starts from radicalization, namely the transmission of radical ideology into a person. The radical understanding included is an ideology that is related to existing extremist ideology and is usually related to certain political groups or religious groups. The most important process in radicalization is in fact the process of giving doctrine to someone by a terrorist group. Once the Doctrine has been given, it becomes difficult to indoctrinate it. It requires a deep understanding of how doctrines are formed and how they are taught. This research describes how the extremist network of a former convict who is now active in deradicalization activities identifies extremist doctrines and ideologies. By understanding the process of identifying doctrines, it will be understood what processes can be carried out to dispel and fight these doctrines to carry out deradicalization. In this study, the case raised is the extremist network experienced by Agus Suprianto alias Farel, in his journey, he went through a process of accepting radical ideology up to extremist ideology, in the end he was deradicalized and is now in the Pancasila ideology which refers to national unity. The provisions are used to carry out empowerment activities and carry out deradicalization efforts.